Therapeutic outcome of various treatment modalities for the management of 34 cases of mandibular unicystic ameloblastoma - Khadka, Rajib; Chaurasia, Nitesh; Yadav, Deepak; Thakurathi, Deepak (Journal of College of Medical Sciences-Nepal, 2018)
Background & Objectives: Unicystic ameloblastoma is a challenge, as conservative modalities have high recurrence chances whereas radical modalities have high morbidity for defects and deformity. Enucleation with peripheral ostectomy and Carnoy’s solution is an intermediate treatment with less risk of recurrence and good outcome. The objectives of the study was to determine the therapeutic outcome for various treatment modalities for the management of mandibular unicystic ameloblastoma. Materials & Methods: Retrospective analysis of 34 cases from 2005 to 2014 was done and were analysed in terms of demographic profiles, treatment modalities and its efficacy (recurrence) in 6 years’ follow up time. Results: The total number of patients was 34. The age ranged from 12 years to 28 years with a mean age of 18.82 years. Gender distribution was 21 males (61.8%) and 13 females (38.2%). The location found was 26 (76.5%) cases in posterior mandibular region and 8 (23.5%) cases in the anterior mandibular region. Size of the lesions was small in 10 (29.4%) cases, medium in 18 (52.9%) cases and large in 6 (17.6%) cases. Perforation of buccal or lingual cortex was present in 6 (17.6%) and no preforation in 28 (82.4%). Treatment modalities done was marsupilisation in 6 (17.6%) cases, enucleation with peripheral ostectomy with caroney solution in 22 (64.7%) cases and resection with safe margin in 6 (17.6%) cases. Recurrence occurred in 8 (23.5%) cases and no recurrence in 26 (76.5%) cases. Conclusion: Enucleation with peripheral ostectomy and Carnoy’s solution is one of the good treatment modality for unicystic ameloblastoma of the mandible whereas complete resection of the mandible with safe margin has low risk of recurrence in long term follow up.